The Relationship Between Parenting Patterns and Body Mass Index (BMI) in Children Elementary School East Jakarta - Mara Imbang Satriawan Hasiolan; Angin, Relita Br Perangin; Toba M.R, Roma Tao; Paturohman, Asep (Nursing Genius Journal, 2024)
Background: Currently many children experience weight problems. So it is important to control the child's body mass index. One of the main actions to handle this problem is through the people closest to them, namely the family. Where children's eating behavior is a reflection of their parents' parenting patterns. In general, each family applies different forms of parenting. Purpose: The aims of study is determine the relationship between parenting patterns and body mass index (BMI) in children at Cipinang 05 Pagi  elementary school, East Jakarta. Methods:   The research method in this study is a cross-sectional study with a purposive sampling technique. With a sample size of 100 students at SDN Cipinang 05 Pagi, East Jakarta. Results: The results showed that the majority of respondents were male 56,0% (n=56), first child 42,0% (n=42), Authoritarian 73,0% (n=73), underweight 59,0% (n=59). There is a significant relationship between parenting patternss and body mass index in school-aged children, p value = 0.002 Conclusion: It is hoped that parents can implement good parenting patterns by not being too pushy about their children in order to shape their children's character, and able to be open in receiving all information about child growth and development care so as to support nutritional status appropriate to the child's age.